2009
DOI: 10.1002/jcb.22199
|View full text |Cite
|
Sign up to set email alerts
|

Notch‐1 signaling is lost in prostate adenocarcinoma and promotes PTEN gene expression

Abstract: Prostate tumorigenesis is associated with loss of PTEN gene expression. We and others have recently reported that PTEN is regulated by Notch-1 signaling. Herein, we tested the hypothesis that alterations of the Notch-1 signaling pathway are present in human prostate adenocarcinoma and that Notch-1 signaling regulates PTEN gene expression in prostate cells. Prostate adenocarcinoma cases were examined by immunohistochemistry for ligand cleaved (activated) Notch-1 protein. Tumor foci exhibited little cleaved Notc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 47 publications
3
52
0
1
Order By: Relevance
“…Upon further examination, microarray analysis revealed that Notch1 and Hey1 genes were significantly down-regulated in prostate adenocarcinoma compared to normal prostate, suggesting that dysregulation of Notch signaling pathway might facilitate prostatic tumorigenesis ). In line with this report, Whelan et al reported loss of total and cleaved Notch1 and Hey1 immunohistochemistry in prostate adenocarcinoma foci (Whelan et al 2009). To further investigate the role of Notch1 signaling in prostate cancer cells, they overexpressed constitutively active Notch1 in the DU145 prostate cancer cell line.…”
Section: Prostate Cancer Hallmarks and Correlation With Notchsupporting
confidence: 56%
See 2 more Smart Citations
“…Upon further examination, microarray analysis revealed that Notch1 and Hey1 genes were significantly down-regulated in prostate adenocarcinoma compared to normal prostate, suggesting that dysregulation of Notch signaling pathway might facilitate prostatic tumorigenesis ). In line with this report, Whelan et al reported loss of total and cleaved Notch1 and Hey1 immunohistochemistry in prostate adenocarcinoma foci (Whelan et al 2009). To further investigate the role of Notch1 signaling in prostate cancer cells, they overexpressed constitutively active Notch1 in the DU145 prostate cancer cell line.…”
Section: Prostate Cancer Hallmarks and Correlation With Notchsupporting
confidence: 56%
“…Moreover, higher Jagged1 expression is significantly associated with recurrence (Santagata et al 2004). However, in the context of cancer etiology, the role of Notch proteins, their ligands and regulation are diverse (Li et al 2007;Shou et al 2001;Wang et al 2006Wang et al , 2010Wang et al , 2011Whelan et al 2009). As reported by Wang et al Notch inactivation might be associated with prostate tumorigenesis .…”
Section: Prostate Cancer Hallmarks and Correlation With Notchmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, studies have shown that Notch signaling could play an anti-tumor role in prostate cancer. 57,58 Multiple studies suggest Notch is a tumor suppressor in context dependent. 59,60 Therefore, deeper investigation is required to explore the function of Notch-1 using transgenic mouse model in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies have reported that Notch 1 signalling regulates PTEN expression in prostate tumors (Palomero et al, 2007;Whelan et al, 2009;Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%